HUBUANGAN KELENTURAN TUBUH TERHADAP KEMAMPUAN MENARI YA SAMAN PADA SISWA KELAS V SD NEGERI 17 PALEMBANG - Amelia Agustini; Endie Riyoko; Treny Hera (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article examines whether there is a relationship between body flexibility and the ability to dance ya saman for the fifth-grade students of SD Negeri 17 Palembang or not. The research is quantitative research with the product-moment correlation research method. The population involved 78 fifth-grade students of SD Negeri 17 Palembang. The research sampling technique used a random sampling technique for class V.c at SD Negeri 17 Palembang. Data collection techniques used tests, observations, and documentation. Data used hypothesis testing, t-test, and determinant test. The results showed that there was a positive and significant relationship between body flexibility and the ability to dance ya saman for the fifth-grade students C of SD Negeri 17 Palembang. It is proven by the product-moment correlation index with an r-count of 0.487, which was at the level of a strong relationship. If it was presented, body flexibility has a relationship in a percentage of 23.71% with the ability to dance ya saman for the fifth-grade students of SD Negeri 17 Palembang. Meanwhile, 76.29% was influenced by other factors that were not tested in the research.